Mixed matrix proton exchange membranes for fuel cells: State of the art and perspectives - Bakangura, Erigene; Wu, Liang; Ge, Liang; Yang, Zhengjin; Xu, Tongwen (Progress in polymer science, 2016)
Proton-conducting mixed matrix membranes (PC-MMMs) have received considerable interest as promising materials that combine the properties of, and create synergism from interactions between, polymeric and inorganic components. The PC-MMM exhibit superior characteristics compared to individual ion-conducting polymeric membranes or free-standing electrolyte inorganic films. Recent advancements in material preparation have enhanced the ability to design PC-MMMs with specified properties. This critical review discusses the progress of the development of PC-MMMs, with special focus on PC-MMMs based on emerging materials, such as porous materials, metal organic frameworks (MOFs), carbon nanotubes (CNTs) and graphene oxides (GOs). Major challenges facing PC-MMMs and strategies taken to overcome those challenges and future perspectives are discussed.